2018
DOI: 10.1111/idj.12385
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ knowledge concerning dental trauma and its management in primary schools in Riyadh, Saudi Arabia

Abstract: There was a lack of knowledge among primary schoolteachers in Riyadh concerning traumatic dental injuries and their management. Statistically significant differences were found among geographical areas, age groups and years of experience; no statistically significant differences were found regarding gender, nationality, marital status, level of education and school type (public/private).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(89 citation statements)
references
References 17 publications
7
63
1
7
Order By: Relevance
“…Various studies have observed insufficient knowledge regarding dental injuries and their emergency treatment procedures in different professional groups who work with children, such as teachers, preschool teachers, physical education teachers and physicians ( 4 - 9 ). Similar results were obtained when medical students, physical education students and dental students were surveyed ( 3 , 8 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have observed insufficient knowledge regarding dental injuries and their emergency treatment procedures in different professional groups who work with children, such as teachers, preschool teachers, physical education teachers and physicians ( 4 - 9 ). Similar results were obtained when medical students, physical education students and dental students were surveyed ( 3 , 8 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of avulsion injuries is often dependent on the decisions and actions taken by attending first‐aiders and inevitably relies on their knowledge of factors such as urgency, manipulation, replantation and transportation. Despite their ideal positioning, school professionals have largely been shown to lack the knowledge and skills required to effectively handle such situations in international cohorts . A similar lack of knowledge in this regard has been found among parents, physical education graduates, fire‐fighters, emergency department physicians and nurses …”
Section: Introductionmentioning
confidence: 91%
“…Despite their ideal positioning, school professionals have largely been shown to lack the knowledge and skills required to effectively handle such situations in international cohorts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] A similar lack of knowledge in this regard doi: 10.1111/adj.12732…”
Section: Introductionmentioning
confidence: 99%
“…Prognóstico e proservação O prognóstico na avulsão dentária muitas vezes é incerto; alguns casos restabelecem a inserção normal, outros se anquilosam e alguns fracassam 41 . No caso de avulsão, o dente deve ser recolocado no alvéolo o mais rápido possível, sem manipular a raiz 42 . Quando colocado antes de 30 minutos, o procedimento tem boa porcentagem de sucesso; depois de 90 minutos, a porcentagem de sucesso atinge somente 7% dos casos 43 .…”
Section: Necrose Pulparunclassified